A Fast Algorithm for Solving Scalar Wave Scattering Problem by Billions of Particles - Ramm, Alexander G.; Tran, Nhan Thanh (World Academic Publishing, 2015)
Scalar wave scattering by many small particles of arbitrary shapes with impedance boundary condition is studied. The problem is solved asymptotically and numerically under the assumptions a d where k = 2 = is the wave number, is the wave length, a is the characteristic size of the particles, and d is the smallest distance between neighboring particles. A fast algorithm for solving this wave scattering problem by billions of particles is presented. The algorithm comprises the derivation of the (ORI) linear system and makes use of Conjugate Orthogonal Conjugate Gradient method and Fast Fourier Transform. Numerical solutions of the scalar wave scattering problem with 1, 4, 7, and 10 billions of small impedance particles are achieved for the first time. In these numerical examples, the problem of creating a material with negative refraction coefficient is also described and a recipe for creating materials with a desired refraction coefficient is tested.
Keywords: Wave Scattering; Small Impedance Particles; Fast Algorithm; Billions of Particles; Negative Refraction; Metamaterials